Induction of Different Apoptosis Pathways by Two Proteusmirabilis Clinical Isolates Strains in Prostatic Epithelial Cells - Fusco, Alessandra; Savio, Vittoria; De Filippis, Anna; Tufano, Antonio; Donnarumma, Giovanna (Frontiers in Physiology, 2018)
Bacterial prostatitis is believed to be the leading cause of recurrent urinary tract infections (UTIs) in men under 50 years of age and occurs both as an acute febrile disease responsive to antibiotics and as a chronic infection that is often unresponsive to antibiotic treatment. Proteus mirabilis is more commonly associated with UTIs in these abnormalities, especially in catheterized patients. This pathogen is capable of colonizing and causing disease due to its virulence factors including fimbriae, flagellar motility, immune avoidance, host-damaging factors, and the ability to form crystalline biofilms. In addition, Proteus lipid A may exhibit apoptotic activity and induce desquamation of epithelial cells. The aim of this work was to evaluate the ability of two clinically isolated strains of P. mirabilis that are phenotypically different, named PM1 of PM2, respectively, to induce apoptosis in human prostatic adenocarcinoma PC-3. Our results demonstrate that PM1 and PM2 are able to activate two different apoptotic pathways, and this different behavior is confirmed by the expression level of the ZapA gene, molecular fingerprinting and different spectrum of antibiotic resistance. The identification and knowledge of relations between the microorganism and host may provide the basis for new solutions to clinical problems with regard to diagnosis and therapy.